1991
DOI: 10.1111/1467-9566.ep10492394
|View full text |Cite
|
Sign up to set email alerts
|

The identification and provision of care for the terminally ill at home by ‘family’ members

Abstract: Audio-recordings of naturally occurring conversations over a three-month period between five nurses in a Symptom Control Team and fifty four terminally ill cancer patients and their relatives in their own homes form the focus of this study. The SCT nurses specialised in the care of the dying but did not carry out 'hands on' nursing which was given by community nurses. The SCT nurses carried out their work through 'talk'. The main aim of the study is therefore, through analysis of the audiorecordings, to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…There is also some suggestion in this research that participants felt socially expected to undertake care‐giving roles. This theme is discussed by Hunt (1991) who suggests that nurses act as social agents to reinforce the spouses’ caring role. However, all of the participants reported that they derived comfort in their bereavement from having undertaken such activities even though they took a toll.…”
Section: Discussionmentioning
confidence: 99%
“…There is also some suggestion in this research that participants felt socially expected to undertake care‐giving roles. This theme is discussed by Hunt (1991) who suggests that nurses act as social agents to reinforce the spouses’ caring role. However, all of the participants reported that they derived comfort in their bereavement from having undertaken such activities even though they took a toll.…”
Section: Discussionmentioning
confidence: 99%
“…Helping people who are suicidal, ill, or traumatized can be the proper remit of either professional or relational category members (cf. Hunt, 1991;Izumi, 2017;Sacks, 1967). However, in the social context of the victim support helpline, a different collection of categories related to victimhood was also relevant in determining the legitimacy of a request for help on behalf.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, caregiving is an activity that lies at the intersection of relational and professional categories. In some cases, participants orient to caring for patients as an obligation of professional category membership, while in others, participants treat caring as a right and obligation of family members (Hunt, 1991;Izumi, 2017). Thus, categories within different collections can be applied to the same people to configure rights or obligations to help in different ways.…”
Section: Entitlement and Obligation To Helpmentioning
confidence: 99%
“…Professional accounts, then, can be understood as contributions to the social construction of the caring community across a variety of physical sites. Hunt (1991b) has shown how this community is sought, but not always found, by nurses visiting the terminally ill at home. The failure to find it can be the source of much regret, involving head shaking about the decline of responsibility in families, and justifying placement in institutional care as a 'safety net'.…”
Section: Professional Concernmentioning
confidence: 99%